A History of Iran: Empire of the Mind by Michael Axworthy (New York: Basic Books, 2008. 249 pages.) (American Journal of Islam and Society, 2009)
This survey of the history of Iranian civilization from ancient times to thepresent is intended for general audiences with little knowledge of Iranianhistory. The book’s nine chapters consist largely of chronological presentationsof political history, but occasionally make room for sections on religiousmovements, society, and the arts. The first two chapters briskly coverthe ancient period through the Sassanids. The third runs from the Islamicconquests through the fifteenth century and contains a long section on theevolution of Persian verse tradition. The fourth and fifth chapters cover theSafavids’ rise and fall, the development of early modern Twelver Shi`ism,and the tumultuous period leading up to the Qajars. The sixth surveys thelate Qajar period and the constitutional revolution, while the last three chaptersdetail the events of the twentieth century with an emphasis on the 1979Islamic revolution and what has happened since. As nearly a third of thebook deals with the twentieth century, the treatment of the ancient periodsand the first millennium of the Islamic era are comparatively spare.Axworthy’s main project is to trace the history of a sense of “Iranianness”or “Irananian identity” that he claims to have identified in ancientsources and uses to justify composing what he calls “a history of Iran.”Although he does not provide an explicit and comprehensive definition ofthis “Iranian identity,” he states clearly that he is not describing a sense ofnation (pp. xv-xvi and 117). Rather, he implies that this identity is a loosesense of affiliation based on the idea of a common land, language, andshared memory. But when he speaks, for example, of an “Iranian revival” inthe second century or an “Iranian reconquest” in the fourteenth, he uses thevery nation-centered paradigm of history that he seeks to avoid, even if herefrains from invoking a “national” sensibility ...